Appropriateness of Orthopedic Surgical Antimicrobial Prophylaxis Prescribing in Australia: Meaningful Metrics for Surgeons. (October 2020) - IERANO, Courtney; Thursky, Karin; James, Rodney
Abstract : Background: Orthopedic procedures are performed at high volumes in Australia. Thus, they are a commonly audited procedure group when measuring surgical antimicrobial prophylaxis (SAP) appropriateness and compliance in Australia and internationally. Recent analysis of the Surgical National Antimicrobial Prescribing Survey (Surgical NAPS) revealed high rates of inappropriateness, both procedurally (39.5%) and postprocedurally (53.0%). Inappropriate use can lead to patient harm and further increases the risk of antimicrobial resistance (AMR). Identification of factors associated with inappropriate orthopedic SAP prescribing may support the development of antimicrobial stewardship (AMS) interventions that are tailored to the orthopedic surgical setting to improve SAP. Methods: Surgical NAPS has been available to all Australian hospitals to complete from 2016; it supports the assessment of SAP appropriateness. Appropriateness is a composite measure based on antibiotic choice, timing of administration, dose and duration, applying the standardized Surgical NAPS Appropriateness Assessment Guide . Logistic regression was used to identify hospital, patient, and surgical factors associated with appropriateness. Adjusted appropriateness (AA) was calculated by generating marginal means from the multivariable model and averaging across all available covariates. Significance for multivariable analysis was determined as P < .05. Additional subanalyses were conducted on smaller subsets to calculate the AA for specific orthopedic procedures. Results: In total, 140 facilities contributed to orthopedic audits in the Surgical NAPS from January 1, 2016, to April 15, 2019, including 4, 032 orthopedic surgical episodes and 6, 709 prescribed doses. Overall appropriateness for prescribed procedural doses (n = 3, 978) was 64.7% and was lower for prescribed postprocedural doses (n = 2, 731, 48.3%). When antimicrobials were not prescribed, appropriateness was higher procedurally (n = 350, 89.7%) and postprocedurally (n = 1, 127, 97.8%). When SAP was indicated, the most common reasons for inappropriateness, when prophylaxis was indicated, were timing for procedural doses (50.9%) and duration for postprocedural prescriptions (49.8%). The AA of each orthopedic procedure group was low for procedural SAP, ranging from 54.1% for knee surgery to 74.1% for total knee joint replacement. The adjusted appropriateness of postprocedural prescriptions was also low, ranging from 40.7% for hand surgery to 68.7% for closed reduction fractures. Conclusions: Orthopedic surgical specialties demonstrated differences across procedural and postprocedural appropriateness. The metric of appropriateness is meaningful for both orthopedic surgeons and AMS programs. Targeted quality improvement projects are needed for orthopedic surgical procedures and to study the engagement between orthopedic surgeons, AMS, and guideline developers to support optimization of antimicrobial use in the surgical setting. Funding: None Disclosures: None